Electrochemistry of Novel Phthalocyanines Bearing 1,2,4 Triazole Groups - KOCA, ATIF (WILEY-V C H VERLAG GMBH, 2020)
The phthalonitrile (3) and triazole substituted metallo phthalocyanines (MPc) (4-7) were prepared. The novel compounds were characterized with spectroscopic data. Electrochemical analyses of metallophthalocyanines (4-7) bearing triazole substituents were performed to investigate redox activity of phthalocyanines (Pcs) ring. While incorporation of Ni(2+)and Cu(2+)cations in the Pc core only influenced peak positions of Pc ring processes, Co(2+)and Cl(1-)Fe(3+)cations of CoPc and FePc gave extra redox couples to the Pc based ones. Releasing the axial Cl(1-)anion on Fe(3+)cation of FePc during the reduction reactions complicated the redox responses. Redox reactions of Co(2+)and Fe(3+)metal centers also considerable influenced spectral and color responses of these complexes.
Keywords: 1; 2; 4 triazole; metallophthalocyanines; electrochemistry; spectroelectrochemistry; SPECTROELECTROCHEMICAL PROPERTIES; METAL-FREE; ELECTROCATALYTIC ACTIVITY; COBALT; COPPER; METALLOPHTHALOCYANINES; SUBSTITUENTS; NICKEL(II); LEAD(II); IRON